Construction of Social Values in Marriage of Arab-Bugis Descent in Pinrang Regency - Muhammad Fadil Wildana, Muhammad Fadil Wildana; Agus Muchsin, Agus Muchsin (IAIN Parepare, 2020)
This study discusses the Construction of Social Values ​​in Arab-Bugis marriages in Pinrang Regency where Arab and Bugis culture have the same background of belief in Islam. Both of them then acculturated in the form of integration of social values ​​and Islamic religious values. The problem is how the adoption of cultural forms in Arab-Bugis marriages, ultimately forms the acculturation and integration of social values ​​in the form of Islamic religious views on the position of women or wives. This type of study is a field study with a qualitative descriptive nature. The primary data of this study comes from informants of Arab descent who marry women from the Bugis tribe, their families, and people from the Bugis tribe who live side by side, have long been associated with Arab descent. Through testing the validity or validity of the data using triangulation techniques. The results of the study show that 1) Marriages between Arabs and Bugis in society in Pinrang Regency have increased in terms of quantity from year to year; 2) Culture in marriage, both Arab and Bugis ethnicity in Pinran Regency, acculturation occurs in the social life of the community, and 3) Constructed an acculturation of marriage culture of Arab descent with the Bugis tribe in realizing social, economic and religious integration so that the harmony of ukhuwah insaniyah and a strong ukhuwah diniyah, a waahidah community and a marhamah (compassionate) community, and a wise (wise) ethnic group and become part of a thayyibah (peace and prosperous) country.